Lipid droplet growth by fusion: insights from freeze-fracture imaging - Robenek, Horst (J Cell Mol Med, 2009)
An understanding of how lipid droplets grow in the cell is important to current human health issues. Homotypic fusion of small lipid droplets to create larger ones is one proposed mechanism though the evidence for this process continues to be debated. By applying the technique of freeze-fracture electron microscopy to cells that have been stimulated to accumulate lipid droplets, we here present images which suggest that at least some large lipid droplets may indeed result from amalgamation of multiple smaller ones. These visual data add significantly to the notion that fusion contributes to lipid droplet growth.